Operations Management Tools for A Resilient, Post-disaster Collaboration System - Aziz, Zubair (2012)
With the frequency of natural and made-made disaster increasing (Asian Disaster Reduction Centre, 2011), understanding and implementing effective recovery and development is vital. The aim of this paper was utilise Operations Management tools for sustainable and collaborative recovery and development. To begin, the disaster operations management industry was discussed and focussed on recovery and development. The challenges of recovery and obstacles to multi-party collaboration emerged from this. Having identified these challenges, ten Operations Management tools were proposed and their suitability to this industry was discussed. Each tools merits and potential was investigated for application in a disaster management context. Having introduced the Operations Management tools, the activities and processes of recovery and development were investigated further. The criticality of collaborative recovery and the need for a collaborative system was analysed and considered. With this in mind, relevant research was proposed. Interview data from practitioner Prof. Salim Sumar as well as extensive literature research was brought forward to contextualise and understand the issues discussed previously and provide a basis for application. In the next section, a holistic and adaptive collaborative system was proposed, complete with an independent, multi-party co-ordination authority. The model for this collaborative system was examined and each stage of this model (Strategic Planning, Analysis, Execution and Implementation, Monitoring and Evaluation) was extensively analysed. For the purposes of this paper, the exemplar application of this model focussed on the provision of sustenance post-disaster in both the short- and long-term. The following chapter detailed how and where the Operations Management tools selected would integrate into the collaborative system proposed. Each stage of the model was discussed in turn along with the detailed application of each tool. The chapter proposed how sustainable recovery and development could be achieved by selecting the appropriate tools for each phase of the system and how the short- and long-term goals linked to operational activities driven by local communities. Before concluding, the paper applied the tools and collaborative system through the context of the 2004 Indian Ocean tsunami. Findings and reports from literature and practitioners served as the context to test the implementation of what had been proposed in this paper. Based on the literature, all the challenges presented could have been avoided or minimised with effective use of these tools and the collaborative system proposed both in the short- and long-term. Whilst a number of broad tools were reviewed, use of one specific tool (Value Stream Mapping) was tested to demonstrate its practical, short-term, effective application. The paper concluded by discussing the need for multi-party collaborative and sustainable recovery that is community-driven where a change in approach is required by all the involved stakeholders. Further application and testing of this collaborative was suggested for future research.